Increasing the effective participation of women in food and nutrition security in Africa - Quisumbing, Agnes R.; Meinzen-Dick, Ruth S.; Smith, Lisa C. (International Food Policy Research Institute, 2004)
What can be done to increase the effective participation of women in food and nutrition security in Africa? This brief advocates a two-pronged approach. First, eradicate discrimination against women, and second, promote catch-up by implementing more active measures in key areas such as control over land, water, and other assets, and investment in education, health, child care, and other services for women. Since the set of actions that are most appropriate in a given situation will be context specific, we present examples of approaches that have worked in Sub-Saharan Africa." -- from Text